This answer is restricted. Please login to view the answer of this question.

Login NowSolution:

f(x, y) = x^{2} + 2y^{2}

such that g(x, y) = x^{2} + y^{2} – 1 = 0

Then

\(∇f = 2x \vec{i} + 4y \vec{j}\)

\(∇g = 2x \vec{i} + 2y \vec{j}\)

Then by Lagrange’s multiplier method, for some scalar λ,

∇f = λ∇g

\(2x \vec{i} + 4y \vec{j} = λ (2x \vec{i} + 2y \vec{j}) \)

This gives

2x = λ 2x

λ = 1

and

4y = λ 2y ⇨ y = 0 [Being λ = 1]

Since we have

g(x, y) = x^{2} + y^{2} – 1 = 0

⇨ x^{2} + 0 – 1 = 0

⇨ x = ± 1

Thus, f attains its extreme at point (1, 0), (-1, 0)

Now,

f(1, 0) = 1 + 0 = 1

f(-1, 0) = 1 + 0 = 1

Thus the extreme value of f is 1.

If you found any type of error on the answer then please mention on the comment or report an answer or submit your new answer.

Click here to submit your answer.

HAMROCSIT.COM

## Discussion